P‐Glycoprotein and Breast Cancer Resistance Protein Transporter Inhibition by Cyclosporine and Quinidine on the Pharmacokinetics of Oral Rimegepant in Healthy Subjects. Issue 7 (19th March 2022) - Bhardwaj, Rajinder; Collins, Julie L.; Stringfellow, Joseph; Madonia, Jennifer; Anderson, Matt S.; Finley, Jeri‐anne; Stock, David A.; Coric, Vladimir; Croop, Robert; Bertz, Richard
Abstract: Rimegepant (Nurtec ODT)—an orally administered, small‐molecule calcitonin gene–related peptide receptor antagonist indicated for the acute and preventive treatment of migraine—is a substrate for both the P‐glycoprotein and breast cancer resistance protein transporters in vitro. We evaluated the effects of concomitant administration of strong inhibitors of these transporters on the pharmacokinetics of rimegepant in healthy subjects. This single‐center, open‐label, randomized study was conducted in 2 parts, both of which were 2‐period, 2‐sequence, crossover studies. Part 1 (n = 15) evaluated the effect of a single oral dose of 200‐mg cyclosporine, a strong inhibitor of the P‐glycoprotein and breast cancer resistance protein transporters, on the pharmacokinetics of rimegepant 75 mg. Part 2 (n = 12) evaluated the effect of a single oral dose of 600‐mg quinidine, a strong selective P‐glycoprotein transporter, on the pharmacokinetics of rimegepant 75 mg. Coadministration with cyclosporine showed an increase in rimegepant area under the plasma concentration–time curve from time 0 to infinity and maximum observed concentration based on geometric mean ratios (90% confidence intervals [CIs]) of 1.6 (1.49‐1.72) and 1.41 (1.27‐1.57), respectively, versus rimegepant alone. Coadministration with quinidine showed an increase in rimegepant area under the plasma concentration–time curve from time 0 to infinity and maximum observed concentration geometric mean ratios (90% CIs) of 1.55 (1.40‐1.72) and 1.67 (1.46‐1.91), respectively, versus rimegepant alone. Strong P‐glycoprotein inhibitors (cyclosporine, quinidine) increased rimegepant exposures (>50%, <2‐fold). In parts 1 and 2, rimegepant coadministration was well tolerated and safe. The similar effect of cyclosporine and quinidine coadministration on rimegepant exposure suggests that inhibition of breast cancer resistance protein inhibition may have less influence on rimegepant exposure.